WHEN POISONED BY TOXIC CHEMICALS MEASURES TO BE TAKEN - Iskanderova Guzal Tulkinovna (Web of Journals Publishing, 2025)
All activities related to land cultivation are carried out in the open air; in times of sharp continental changes in weather conditions, the impact of certain meteorological conditions on people engaged in agricultural work is of great importance, affecting thermoregulation, the general condition of workers, their efficiency, and the level of disease.
Keywords: Chemicals, poisoning, measures to be taken, first aid, pesticides.